Building bridges between the community, the University and the Municipal Museum Casa de Florentino Ameghino from Luján through its cultural peritage (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
A critical reflection is made on the results obtained after the implementation of an extension project developed between the National University of Luján and the Casa del Florentino Ameghino Municipal Museum of the city of Luján. The general objective of this project was to promote a critical and reflective understanding of the local population about the elements that make up the archaeological and paleontological Cultural Heritage of the upper and middle basin of the Luján River, as a necessary part of its sustainable management. The classification and analysis of the Cultural Heritage of the Museum's heritage was provided for its enhancement and content was provided to the exhibitions, workshops and outreach activities of the institution, taking the collections as the axis as articulators of the exchange of knowledge between different actors and public. It also reflects on the pending challenges for local museums in general to become self-sustaining institutions and generators of superior knowledge.
Keywords: archaeology; paleontology; community; heritage; megafauna; museum